2002
DOI: 10.5038/2375-0901.5.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Bus Rapid Transit: An Overview

Abstract: Bus Rapid Transit (BRT) is growing in popularity throughout the world. The reasons for this phenomenon include its passenger and developer attractiveness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
85
0
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 0 publications
0
85
0
16
Order By: Relevance
“…The exception to this rule, however, could be BRT wherein buses are provided with an exclusive, dedicated lane, signifying a significant improvement in service quality in the minds of real-estate developers and property owners (Polzin and Baltes, 2002). Levinson (2002) contends that BRT investments in Ottawa, Pittsburgh, Brisbane, and Curitiba generated land-use benefits that…”
Section: Literature Reviewmentioning
confidence: 99%
“…The exception to this rule, however, could be BRT wherein buses are provided with an exclusive, dedicated lane, signifying a significant improvement in service quality in the minds of real-estate developers and property owners (Polzin and Baltes, 2002). Levinson (2002) contends that BRT investments in Ottawa, Pittsburgh, Brisbane, and Curitiba generated land-use benefits that…”
Section: Literature Reviewmentioning
confidence: 99%
“…Frequent all-day services that need to operate at least for 16 hours per day with peak headways of 10 min or less [53]. 7.…”
mentioning
confidence: 99%
“…This research attempted to define the level of service characteristics at which point a system can be considered "bus rapid transit" and found that BRT is growing in popularity due to its cost effectiveness and the fact that it can be adapted for use in conventional bus systems (Vuchic 1992;Jarzab et al 2002;Levinson et al 2002). Additionally, the Institute for Transportation Policy (ITDP), a non-profit organization that provides technical assistance on public transportation projects and advocates for BRT development, has developed a ranking system for comparing BRT systems and determining whether a system meets their standards for what can be considered "true" BRT (Weinstock et al 2011).…”
Section: Literature Reviewmentioning
confidence: 99%